Spatial policy for a competitive regional system: Economic and social infrastructure elements - Daisuke Nakamura (Journal of Urban Management, 2013)
The optimal formation of regions changes over time, which prompts the question: how can regions survive by expanding their unique competitive advantages? One of two key factors cited in response to this question is competitive economic forces related to economic infrastructure elements. The other is attractiveness, which is relevant to social infrastructure elements. The first part of this paper explores elements of the former, dealing with localisation and activity-complex economies from the standpoint of agglomeration economies. The second part examines elements of the latter, such as attractiveness of large metropolitan areas where positive and negative aspects of urbanisation economies and diseconomies coexist. The final part of the paper offers an integrated framework that features both economic and social infrastructure elements, indicating how a sustainable regional system can be coordinated.
Keywords: D62; H11; O18; R12; 330; agglomeration economies; infrastructure; Spatial organisation; sustainable regional growth; welfare